Linear and three-dimensional volumetric analysis of maxillary sinus in Saudi Arabian population: A cone-beam computed tomography study - Anuroop Singhai; Harshkant Gharote; Mohamad Abdulhamid AlAbrash; Raghad Saad AlRajhi; Ranya Qasem Abdullah; Haya Ahmed AlWatban (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: The maxillary sinus presents as an important anatomical structure and understanding its radiographic anatomy is crucial for surgical procedures such as dental implant placement and extractions. Measuring the linear and volumetric dimensions of the maxillary sinus is essential for accurate treatment planning and a favorable outcome. Forensic odontology requires population-specific data for victim identification. There is therefore some need to develop a multicentric, multiethnic data registry. Purpose: The present study evaluates and compares the dimensions of maxillary sinuses and their relationship with individual height in the Saudi Arabian population, using cone-beam computed tomography (CBCT). Methods: The study subjected CBCT scans of 30 individuals to linear and volumetric analysis. The measurements were taken by two observers and mean dimensions were used for the analysis. Linear and volumetric dimensions were measured for the total sample and male (n=11) and female (n=19) categories. Results: Differences between linear and volumetric dimensions were statistically nonsignificant for males, females, and the overall sample. Correlations between left- and right-sinus dimensions were significant within females and the overall group. There was weak association between individual height and maxillary sinus dimensions. Conclusion: There is no significant variation between right and left maxillary sinus dimensions among the Saudi Arabian population. A negative correlation was observed between overall height and left maxillary sinus volume in both genders, and with right sinus volume in females only.